từ gt:(a+b+c)2=0⇒a2+b2+c2=−2(ab+bc+ca)Ta có:⇔2(a4+b4+c4)=(a2+b2+c2)2⇔a4+b4+c4=2(a2b2+b2c2+c2a2)⇔(a2+b2+c2)2=4(a2b2+b2c2+c2a2)$\Leftrightarrow [-2(ab+bc+c^2a)]^2=4(a^2b^2+b^2c^2+c^2a^2)⇔4(a2b2+b2c2+c2a2)+8(a2bc+b2ca+c2ab)=4(a2b2+b2c2+c2a2)\Leftrightarrow 8abc(a+b+c)=0(đpcm)$
từ
gt:(a+b+c)2=0⇒a2+b2+c2=−2(ab+bc+ca)Ta có:
⇔2(a4+b4+c4)=(a2+b2+c2)2⇔a4+b4+c4=2(a2b2+b2c2+c2a2)⇔(a2+b2+c2)2=4(a2b2+b2c2+c2a2)⇔[−2(ab+bc+ca)]2=4(a2b2+b2c2+c2a2)⇔4(a2b2+b2c2+c2a2)+8(a2bc+b2ca+c2ab)=4(a2b2+b2c2+c2a2)⇔8abc(a+b+c)=0(đpcm)